Evaluasi Pelaksanaan Proyek Kapal X Di Perusahaan Galangan Kapal Menggunakan Software Microsoft Project dan S-Curve - Pangestika Oirala Kawuri; Moch. Tutuk Safirin (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Working on a project requires careful planning, so that it can be carried out with optimal time and cost. However, in practice, the implementation of project work usually encounters obstacles that cause schedule delays which result in cost overruns. Therefore, to determine the accuracy of the implementation of a project, routine evaluation and analysis is carried out with the aim of knowing how the progress of a project is progressing. In this research, the Earned Value Analysis method is used to examine trends in schedule variance and cost variance in a period (time) during the project. Based on the calculations and analysis carried out, it can be concluded that there were no delays in the implementation of the Kapal X construction project at X company, the work was carried out according to the predetermined schedule, even faster than the previously planned schedule. Based on the results of the analysis of project completion projections in terms of time, the results for the projected remaining work time (ETS) were 268 days and for the projected total project completion time to completion (EAS) it was 594 days or 306 days faster than the initial plan of 900 days.